Public Administration in the Sphere of Tourism and Yachting - Vadim Viktorovich Volostnykh (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
An article is devoted to the problem of human potential development through the life quality increasing. Nowadays several critical public weal sources are deprived of state care and protection. The subsequent problems are analysed on the base of yachting and nautical tourism. Different approaches to obtain an executive power support from the ministries - emergency situation, transport and tourism (culture) are considered. The possible future merger between yachting and tourism industry is evaluated in light of modern trends.